Bowdoin School on Myrtle Street, ca. 1865 - Hawes, Josiah Johnson (Tufts Archival Research Center, 2005)
Street-level view northeast of the Bowdoin School on Myrtle Street, located between S. Russell Street to the east and Irving Street to the west. The facade of the school faces south towards Myrtle Street. The west elevation of the school faces Irving Street, which is visible along the left side of the photograph. Street-lights adorn the facades of other buildings lining both the north and south sides of Myrtle Street, which is visible along the lower-right side of the photograph. 6 3/4 in diameter, 6 7/8 x 6 15/16 overall Photographs